Efeitos da radioterapia sobre as condições bucais de pacientes oncológicos - Gaetti-Jardim Júnior, Elerson [UNESP]; Sousa, Fátima Regina Nunes de [UNESP]; Gaetti-Jardim, Ellen Cristina [UNESP]; Castro, Eni Vaz Franco Lima de [UNESP]; Ciesielski, Francisco Isaak Nicolas [UNESP]; Buso-Ramos, Marcelle Marie [UNESP]; Okamoto, Ana Cláudia [UNESP]; Crivelini, Marcelo Macedo [UNESP]; Castro, Alvimar Lima de [UNESP] (My University, 2011)
This study evaluated the oral conditions of 50 cancer patients undergoing head and neck radiotherapy (RT). Clinical examinations were performed before treatment, immediately after 30 days after RT and 6 months after conclusion of RT. Periodontal conditions were evaluated using the criteria of the Periodontal Screening and Recording (SRP) and the need for dental treatment were determined. The presence of xerostomia, mucositis and other side effects of RT were also evaluated. Soon after the beginning of RT, the irradiated patients of radiotherapy developed severe mucositis, dermatitis, dysgeusia, xerostomia and, to a lesser extent, candidosis. After completion of radiotherapy, 68% of patients had level III or IV mucositis. It was found that the development of mucositis hinders oral hygiene and these factors contribute to exacerbate inflammation of periodontal tissues. The data from this study evidenced that the main cause of desertion of RT and of severity of sequelae of RT depends on the oral conditions of patients before starting treatment and the absence of previous dental treatment prior RT.

O presente estudo avaliou as condições bucais de 50pacientes oncológicos submetidos à radioterapia de cabeçae pescoço (RT). Os exames clínicos foram realizados antesdo tratamento, imediatamente após 30 dias da RT e 6 mesesapós a conclusão da RT. As condições periodontais foramavaliadas segundo os critérios do Periodontal Screeningand Recording (PSR ) e determinou-se a necessidade detratamento odontológico. A presença de xerostomia, mucositee outros efeitos colaterais da RT foi também avaliada.Os pacientes irradiados logo após o início da radioterapiadesenvolvem severa mucosite, dermatite, disgeusia, xerostomiae, em menor extensão, candidose. Após a conclusãoda radioterapia, 68% dos pacientes apresentavam mucositegrau III ou IV. Verificou-se que o desenvolvimento de mucositedificulta a higiene bucal, o que colabora para exacerbara inflamação nos tecidos periodontais. Os dados do presenteestudo mostraram que a principal causa de abandono daRT e da severidade das sequelas da RT dependem das condiçõesbucais dos pacientes antes do início do tratamento eda ausência de tratamento odontológico prévio à RT.
Effects of radiotherapy on the oral conditions of oncologic patients
Keywords: Head and neck neoplasms; Radiotherapy; Mucositis; Neoplasias de cabeça e pescoço; Radioterapia; Mucosite